“Evaluación de diferentes dosis de ácido piroleñoso para el control de las principales plagas en el cultivo de pimiento (Capsicum annum L)”. - Espín Carvajal, Dalember Reeven (2020)
The present work carried out confirms the obligation to seek an optional, ecological and practical treatment for the control of the main pests in the pepper crop (Capsicum annum L), the same ones that affect national production. All these insects have a short biological cycle and accelerated reproduction, this leads to an inefficient control of them, for which, it was proposed as a general objective to determine the different doses of pyroliginous acid for the control of the main pests in the cultivation of the bell pepper (Capsicum annum L). The investigation was carried out at the “Dos Hermanos” farm, in the Mocache canton, Los Ríos province, owned by Mr. Heriberto Espín, located in the Aguas Frías Campus, Km 17 Vía Ventanas-Mocache. The Random Complete Blocks (BCA) design was applied with four repetitions and five treatments. The application of the doses in the implemented treatments: low dose Pyroligneous acid 1Lt/Ha-1, medium Pyroliginous acid 2Lt/Ha-1 and high Pyroliginous acid 3Lt/Ha-1, the chemical control of 0.1Lt/ha-1 and the absolute control each one respectively, presenting the treatment with medium dose; a yield of $ 2555.47 kg/ha-1. To evaluate the phytotoxicity of the product, it was carried out in the aforementioned treatments during the entire vegetative stage of the crop in open field, for this the phytotoxicity scale provided by Bayer was used, by which it was deduced that the plants presented 0% phytotoxicity, each of the treatments studied. The results based on the production, it was observed 100% healthy plants within the useful area, with a low presence of insects, around 5%, Treatment 2 presented height homogeneity throughout the investigation, maintaining this characteristic until the first harvest with a height of 49.3 cm, the results showed that the T2 registered a gross income of $ 5110.94, obtaining a benefit / cost of $ 1.86. It is important to mention that these data are the result of the first harvest of the crop. Keywords: Rice husk, flowering, Abamectin